IMPACT OF ARTIFICIAL INTELLIGENCE ON COMMERCIAL BANK’S ATM - Adhikari, R. P.; Aryal, T.; Park, G. (Farabi Journal of Social Sciences, 2022)
Artificial Intelligence (AI) is a rapidly growing area that has been getting the greatest attention in the business including the banking sector. AI has huge applications in the area of commerce, education, transportation, banking as well as daily life. AI in the banking industry relies on faster inexpensive, more accurate, and efficient work at the banking sector. By using AI in commercial banks, the banker gets more benefits and audience response positive as well as strong competition in work efficiency. AI provides renovating ideas to promote the banking sector through Automated Teller Machines (ATM). In this research paper, the impact of AI in the commercial bank ATM sector has been discussed with primary data collected from five banks and 30 ATMs from the perspective of clients. It was found that AI on ATMs has a positive impact as it gives excellent client service, high work efficiency, and security. Keywords: Artificial Intelligence, ATM, Commercial Banks, efficiency, security.